The Influence of Organizational Culture, Work Discipline and Communication on Employee Performance - Stefanny Indah Rheksa; Reza Kurniawan; Irwana Hidayat (Green Publisher Indonesia, 2025)
The purpose of this study was to determine the effect of organiational culture, work discipline, and communication on employee performance. The object selected in this study is PT. Wahana Andika Mandiri, a company engaged in transportation and logistics. The analysis technique used is multiple linear regression analysis. The form of research used in this study is descriptive and causal. The population in this study were employees of PT. Wahana Andika Mandiri, totaling 105 employees, with the number of samples used as many as 105 employees. The saturated sampling technique was collected by conducting a questionnaire. The results of this study ultimately indicate that organizational culture, work discipline and communication have an influence on employee performance.